Interface engineered HfO2-based 3D vertical ReRAM. (29th April 2016) - Hudec, Boris; Wang, I-Ting; Lai, Wei-Li; Chang, Che-Chia; Jančovič, Peter; Fröhlich, Karol; Mičušík, Matej; Omastová, Mária; Hou, Tuo-Hung
Abstract: We demonstrate a double-layer 3D vertical resistive random access memory (ReRAM) stack implementing a Pt/HfO2 /TiN memory cell. The HfO2 switching layer is grown by atomic layer deposition on the sidewall of a SiO2 /TiN/SiO2 /TiN/SiO2 multilayer pillar. A steep vertical profile was achieved using CMOS-compatible TiN dry etching. We employ in situ TiN bottom interface engineering by ozone, which results in (a) significant forming voltage reduction which allows for forming-free operation in AC pulsed mode, and (b) non-linearity tuning of low resistance state by current compliance during Set operation. The vertical ReRAM shows excellent read and write disturb immunity between vertically stacked cells, retention over 10 4 s and excellent switching stability at 400 K. Endurance of 10 7 write cycles was achieved using 100 ns wide AC pulses while fast switching speed using pulses of only 10 ns width is also demonstrated. The active switching region was evaluated to be located closer to the bottom interface which allows for the observed high endurance.